Palindromic units are part of a new bacterial interspersed mosaic element (BIME). - Gilson, E (1991)
Palindromic Units (PU or REP) were defined as DNA sequences of 40 nucleotides highly repeated on the genome of Escherichia coli and other Enterobacteriaceae. PU are found in clusters of up to six occurrences always localized in extragenic regions. By sorting the DNA sequences of the known PU containing regions into different classes, we show here for the first time that, besides the PU themselves, each PU clusters contains a number of other conserved sequence motifs. Seven such motifs were identified with the present list of PU regions. Remarkably, each PU cluster is exclusively composed of a mosaic combination of PU and of these other sequence motifs. We demonstrate directly by hybridization experiments that one of these motifs (called L) is indeed present at a large number of copies on the Escherichia coli chromosome and that its distribution follows the same species specificity as PU sequences themselves. We propose that the mosaic pattern of motif combination in PU clusters reveals a new type of bacterial genetic element which we propose to call BIME for Bacterial Interspersed Mosaic Element. The Escherichia coli genome contains about 500 BIME.